Innerselfie: can we use Immersive Virtual Reality to change cancer risk perceptions and promote physical activity in young people? - Abi Fisher; Susanne Meisel; Thomas Webb; Bernadette Fisher; Chloe Cooke; Katie Newby (Frontiers Media S.A., 2015)
Background: There is strong evidence that being physically active reduces the risk of colon cancer. Emerging evidence suggests that physical activity (PA) even in the teenage years may impact on colon cancer risk. However, levels of activity in young people are currently low, with around half of UK school children not meeting even minimum UK Government guidelines for health. Innovative interventions are urgently required. Young people may not perceive themselves to be 'at risk' for colon cancer (usually diagnosed >65 years). However it feasible that modifying underlying beliefs about cancer risk, whilst simultaneously enhancing PA self-efficacy, could lead to sustained PA behaviour change. Immersive virtual reality (IVR) is a novel technology that has the potential to be used in this context; however, this has yet to best tested. Aims: The overarching aim of the Innerselfie project is to test the hypothesis that a theory-based intervention incorporating IVR, delivered to children aged 13-17 years can (i) change risk and efficacy appraisals and (ii) promote sustained changes in PA. Methods: Given the entirely novel nature of this work, and in line with the MRC framework of designing and evaluating complex interventions, three phases are proposed.. Phase I: The exploratory phase (for which the current funding has been obtained), Phase II: the build/test and development phase and Phase III: a randomised controlled trial to determine efficacy by measuring IRR beliefs, risk and efficacy appraisals, activity levels and relevant cancer biomarkers. Results: Phase I is currently underway and has involved identifying an appropriate partner company with expertise in IVR, collecting qualitative data on colon cancer risk perceptions from young people (thematic analyses currently underway), assembling a steering committee, as well as conducting workshops with our Young People's Partnership Board (YPPB) to get continuous feedback on creative ideas. Conclusions: This is a novel exploratory study that is still underway, and the presentation will outline the Innerselfie project and summarise findings to date.